Sleep Quality and its Correlation with Glycosylated Hemoglobin Level among Patients with Type 2 Diabetes Mellitus - Vijayan, Geethu; Deepa, P. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim was to assess the sleep quality and its correlation with glycosylated hemoglobin level among patients with type 2 diabetes mellitus. Background: A systematic review and meta-analysis on impact of sleep amount and sleep quality on glycemic control, including 70,000 type 2 diabetes mellitus patients with 20 studies, revealed that there was 23% increase in HbA1c level in patients who reported insufficient sleep duration <4.5–6 h/night. Methods: A correlational research design was used. The sample consisted of 120 adults with type 2 diabetes mellitus attending non-communicable disease clinics of a rural and urban Health Training Center in Alappuzha. Socio-personal and clinical data were collected by interviewing the participants. Pittsburgh Sleep Quality Index (PSQI) scale used for assessing subjective sleep quality. The glycosylated hemoglobin level of the patients was estimated. Results: It was found that 63.3% of patients with type 2 diabetes mellitus had poor sleep quality. There was a moderate positive correlation (r = +0.651 P < 0.01) between sleep quality and glycosylated hemoglobin level among patients with type 2 diabetes mellitus. Out of seven domains in PSQI scale, six domains had positive correlation with glycosylated hemoglobin level. Conclusion: It can be concluded that it is imperative to assess sleep in all patients with type 2 diabetes mellitus to identify and address poor glycemic control and this can, in turn, help to improve the quality of life of patients with type 2 diabetes mellitus.